CURATE.AI Digital Therapeutics: Harnessing CURATE.AI as a Digital Therapeutics Platform by Identifying N‐of‐1 Learning Trajectory Profiles (Adv. Therap. 9/2019). Issue 9 (13th September 2019) - Kee, Theodore; Weiyan, Chee; Blasiak, Agata; Wang, Peter; Chong, Jordan K.; Chen, Jonna; Yeo, B. T. Thomas; Ho, Dean; Asplund, Christopher L.
Abstract : The field of digital therapeutics represents a gateway towards using artificial intelligence to optimize software‐based interventions. In article1900023, Dean Ho, Christopher L. Asplund and co‐workers integrate CURATE.AI with the Multi‐Attribute Task Battery (MATB) platform in a prospective pilot study to identify N‐of‐1 profiles as foundations for dynamically personalized learning and cognitive training. Image credit: Zac Goh, National University of Singapore